Comparison of the beef empire days index with carcass pricing for ranking beef carcasses - King, D.A.; Jones, R.D.; Schafer, D.E.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Our study evaluated the effectiveness of the Beef Empire Days carcass index in ranking beef carcasses compared to rankings based on carcass prices. Two price sets were used: the average prices between January 1998 and June 2001, and a short-range price determined from the average prices between April and September of 2001. Additionally, carcass data from the top live-placing cattle were compared to the data of the highest indexing carcasses. The live show judges were very accurate in selecting for ribeye size. However, they selected cattle that were fatter, but did not marble as well as the high indexing carcasses. Changes that might improve the index are identified. However, the Beef Empire Days index ranked carcasses moderately well compared to the pricing system.
Keywords: Beef; Beef carcass ranking; Prices